Factors Affecting Students' Speaking: is Motivation the Most Influencing Factor? - Muliani Muliani; Muhammad Muhlisin; Zainul Islam (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Abstract The phenomenon that the students of English Department, at Universitas Pendidikan Mandalika were not active to speak outside the class using English as their target language triggered this research to be conducted. They tend to go back to their first language (Bahasa Indonesia) as they are outside the classroom while motivation can be seen as the successful aspect when learning a target language deals with speak the language (speaking skill) (Ihsan, 2016:32). This research deals with 10 factors affecting learners in learning the target language (Pasty and Nina: 2006) in which this aims at finding the percentage of the factors affecting the learners’ speaking. By means of applying questionnaire and interview to 15 subjects of the research it was found that all ten factors were found as the factors affecting the students’ speaking. The result shows that motivation is the most influencing factor with the highest percentage among the other factors (57%). This means that the students are actually having high motivation to speak English not only during the class, but also after the class, but it cannot be neglected that the other 9 factors (age, aptitude, personality, attitude, cognitive style, learning style, intelligent, anxiety, and group affiliation) are also affecting the learners’ speaking. Moreover, the result shows that the 10 factors cannot be separated affecting the learners, but they are well interrelated. Thus, it can be concluded that motivation takes the position as the most influencing factor affecting students’ speaking outside the classroom as this factor is also well supported by the other nine (9) factors. Keywords:Motivation; Speaking; Factors Affecting L2 Learning